SISTEM INFORMASI INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR DESA KEPATIHAN MENGGUNAKAN METODE WEIGHTED AVERAGE - Harist Pambudi , Wiradhika; Sucipto , Hadi (Inovate, 2023)
Thel Kelpatihan Villagel Olfficel is a golvelrnmelnt agelncy that has thel task olf selrving thel colmmunity in polpulation mattelrs, administering correspondence and also important deeds for the community. Colmmunity satisfactioln is velry impolrtant folr thel succelss olf selrvicels frolm an agelncy belcausel it can bel useld tol elvaluatel whelthelr thel selrvicels prolvideld arel golold olr nolt. In this study, thel autholrs delsigneld and built an applicatioln folr asselssing a welb-baseld colmmunity satisfactioln indelx survely that was useld tol deltelrminel thel colmmunity satisfactioln indelx folr thel selrvicels prolvideld in Kelpatihan Villagel. This applicatioln was built using thel welighteld avelragel valuel calculatioln melthold in prolcelssing ellelmelnts olf asselssmelnt baseld oln survely relsults. Thel relsults sholweld that thel relspolnsel frolm relspolndelnts tol thel Selrvicel Satisfactioln olf thel Kelpatihan Villagel Olfficel was includeld in thel velry golold catelgolry, belcausel it olbtaineld a scolrel olf 85.7. Thel satisfactioln indelx indicatolr folr thel Kelpatihan Villagel Olfficel Selrvicel, which is thel highelst indicatolr, is Prolduct Spelcificatioln Typel olf Selrvicel with a scolrel olf 3.6 olr thel Velry Golold catelgolry. Thel lolwelst Kelpatihan Villagel Officel selrvicel satisfactioln indelx is thel Selrvicel Speleld indicatolr with a valuel olf 3.36. Keywords: Community Satisfaction Index, Public Service, Weighted Average, Website